2016
DOI: 10.1097/gox.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Closure after TRAM Flap Breast Reconstruction with Transversus Abdominis Muscle Release and Mesh

Abstract: Summary:Breast reconstruction with a pedicled transverse rectus abdominis muscle (TRAM) flap can result in significant abdominal wall donor-site morbidity. Although the pedicled TRAM flap donor area reinforced with mesh results in decreased rates of postoperative abdominal bulging and hernias, the best technique to accomplish that is yet to be elucidated. We present our novel technique of posterior components separation with transversus abdominis muscle release and retromuscular mesh reinforcement for donor-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In patients with DIEP flaps, the use of mesh in the repair of the abdominal donor site may also reduce the rate of postoperative abdominal bulge 14 . In previous studies on patients with autologous breast reconstruction using abdominal tissue, mesh has been placed in a variety of different positions, such as anterior (overlay) or posterior (sublay) to the rectus abdominis muscle or in a bridging position between the rectus abdominis muscles (inlay) 10,11,15,16 . However, the choice of mesh position has been determined by the preference of the surgeon, relying on personal experience and anecdotal evidence from published case series, as comparative studies investigating donor site complications among patients with different mesh positions have not been performed so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with DIEP flaps, the use of mesh in the repair of the abdominal donor site may also reduce the rate of postoperative abdominal bulge 14 . In previous studies on patients with autologous breast reconstruction using abdominal tissue, mesh has been placed in a variety of different positions, such as anterior (overlay) or posterior (sublay) to the rectus abdominis muscle or in a bridging position between the rectus abdominis muscles (inlay) 10,11,15,16 . However, the choice of mesh position has been determined by the preference of the surgeon, relying on personal experience and anecdotal evidence from published case series, as comparative studies investigating donor site complications among patients with different mesh positions have not been performed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al 9 showed that the rate of abdominal bulging or hernia after MS-TRAM reconstruction without mesh was approximately 11% and was reduced to 5% when synthetic mesh was incorporated into the donor site repair, then being comparable with the rates observed in patients with DIEP flap reconstructions. A variety of different mesh positions in relation to the rectus abdominis muscle have been used to reinforce the donor site after MS-TRAM or DIEP harvest 10,11 . However, whether the plane of mesh placement has an impact on donor site complications in patients undergoing breast reconstruction with abdominal free flaps has not been investigated so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, we opted for the TRAM flap 21 , trying however to enlarge the skin envelope as much as possible using a T-inverted design, in order to cover the extensive loss of substance. Partial drawbacks of this flap are potential herniations, that could be overcome with adequate mesh positioning at donor site 22 .…”
Section: Discussionmentioning
confidence: 99%
“…[10,16,17] The use of mesh is demonstrated to reduce the risk of abdominal hernia and bulging. [11,[18][19][20][21] An extreme example of abdominal rupture following DIEP flap harvest is discussed by Iwabu et al [22] Authors report the patient required emergent surgery, which consisted of primary fascial repair with mesh overlay placement. [22] This series of patients also demonstrated a significant difference in the rates of polypropylene mesh and biologic mesh use.…”
Section: Discussionmentioning
confidence: 99%